Система підготовки особового складу військ СС нацистської Німеччини напередодні та в роки Другої світової війни (1933–1945 рр.) - Гетьманчук, Микола; Hetmanchuk, Mykola (Lviv Politechnic Publishing House, 2019)
Проаналізовано особливості системи бойової підготовки солдатів та офіцерів військових формувань СС напередодні та в роки Другої світової війни. Особливу увагу звернуто на підготовку офіцерських кадрів у військових навчальних закладах СС. Розкрито зміст нових методів підготовки та їх впровадження у процесі навчання солдатів та офіцерів військ СС.

The issue of the combat training system of soldiers and officers of the SS military units of Nazi Germany on the eve of and during the Second World War has been studied. The content of new training methods and their introduction into the training process of soldiers and officers of the SS, developed by F. Steiner, C. Freiherr von Montigny, P. Hausser, has been revealed. Special attention is paid to the training of officers and non-commissioned officers of the SS forces. It was shown that during the 1933–1945 period, 52 junker (officers), non-commissioned officers and specialized schools, 13 training camps were created for the training of SS personnel. It is noted that the total number of officers in the SS troops in 1934– 1945 was 26,100 (of which 17,000 graduated from Junker schools, foreign army officers, 3,400 officers who received the title for courage in battles, 2,000 officers transferred from the police). It is stated that it was thanks to Junker schools that the SS troops received the most advanced system of military training during the Second World War. High professional training of SS officers qualitatively distinguished them in comparison with the officers of the Red Army and Аllied officers. It is noted that the developed new method of training SS ordinary soldiers provided for a gradual complication of the training process in the development of small arms, techniques, physical training, hand-to-hand combat, orientation on the ground, working with maps, digging and camouflaging, climbing training, and overcoming water obstacles. It is especially emphasized that all SS soldiers and officers were ideologically motivated because they belonged to the Nazi party units (NSDAP), and thus «party comrades» regardless of military titles. Therefore, the SS soldiers subordinated to the officers consciously, and not only at the expense of discipline. It is argued that from all components of the Third Reich Armed Forces the SS troops, due to the high level of professional training, are assessed as most effective in land-based military operations. They, as a rule, avoided outdated combat tactics, quickly assimilated the latest achievements in the field of military equipment.
SS troops personnel training system of nazi Germany before and during the World War II (1933–1945)
Keywords: Третій рейх; Друга світова війна; війська СС; школи СС; методи підготовки військ СС; ідеологія СС; Third Reich; Second World War; SS troops; SS schools; SS training methods; SS ideology; 94 (100); 355. 318. 2 (430)